2022
DOI: 10.3389/fphar.2022.831364
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Utility Analysis of Once-Weekly Semaglutide, Dulaglutide, and Exenatide for Type 2 Diabetes Patients Receiving Metformin-Based Background Therapy in China

Abstract: Introduction: The substantial financial burden associated with type 2 diabetes (T2D) over a lifetime cannot be neglected. Therefore, the objective of this study was to evaluate the pharmacoeconomic value of three once-weekly GLP-1 RAs, namely subcutaneous semaglutide (sc. SEMA), dulaglutide (DULA), and extended-release exenatide (e-r EXEN), in treating patients with T2D that cannot be controlled with metformin-based background therapy, and to find a suitable price reduction for non-cost-effective medications, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…SEMA was not approved for the Chinese market by the National Medical Products Administration until 2021. According to our previous research, 17 SEMA did not appear to be cost‐effective versus DULA when SEMA first entered the Chinese market at a relatively high price.…”
Section: Introductionmentioning
confidence: 83%
“…SEMA was not approved for the Chinese market by the National Medical Products Administration until 2021. According to our previous research, 17 SEMA did not appear to be cost‐effective versus DULA when SEMA first entered the Chinese market at a relatively high price.…”
Section: Introductionmentioning
confidence: 83%
“…Compared with previous similar studies ( 2 , 53 , 54 ), our study has the following advantages. First, we are the first to systematically compare the efficacy and cost-effectiveness of GLP-1RAs approved in China, thereby providing comprehensive evidential support for clinical rational drug use and medical service decision-making.…”
Section: Discussionmentioning
confidence: 83%
“…Currently, there are few research articles on the cost-effectiveness of GLP-1RAs. Hu et al ( 53 ) evaluated the cost-effectiveness of semaglutide, dulaglutide, and extended-release exenatide in treating patients with T2DM which cannot be controlled with metformin-based background therapy. They found that dulaglutide appeared to be the most cost-effective option, which was consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
“… 9 It has been widely used to treat T2DM in China, especially in patients who are overweight or obese. 10 Although the subgroup analysis of the AWARD studies showed that dulaglutide significantly improved glycemic control, reduced the risk of weight gain and had acceptable gastrointestinal side effects in the Chinese population, 11 , 12 research data on dulaglutide in the Chinese population are limited. The obesity profile and fat distribution of the Chinese population are different from those of the European and American populations considering ethnic and dietary characteristics.…”
Section: Introductionmentioning
confidence: 99%